2019
DOI: 10.1017/s1460396919000487
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective observational study to estimate set-up errors and optimise PTV margins in patients undergoing IMRT for head and neck cancers from a Government cancer centre of Eastern India

Abstract: Background:The head and neck cancers as a whole are the most common cancers among males in India. Technological advancements have led to an improvement in radiation therapy (RT) techniques with subsequent reduction in normal tissue complications. To correct patient set-up errors, an off-line correction method like no action level (NAL) protocol may be used as a preferred protocol particularly for a busy department. The objectives of the study were to measure the translational set-up errors using kV cone-beam c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…However, Delishaj et al [8]] discovered that the systematic and random errors were under 0.2 cm. The outcome was comparable to research by Biswas et al [5], who discovered that all translation directions utilising CBCT had mean systematic and random errors of less than 0.2 cm. They claim that knowing these mistakes is essential for figuring out PTV margins, couch correction tolerance limits, and plan adaptation in HNC radiation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, Delishaj et al [8]] discovered that the systematic and random errors were under 0.2 cm. The outcome was comparable to research by Biswas et al [5], who discovered that all translation directions utilising CBCT had mean systematic and random errors of less than 0.2 cm. They claim that knowing these mistakes is essential for figuring out PTV margins, couch correction tolerance limits, and plan adaptation in HNC radiation.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Biswas et al [5] investigated the frequency and magnitude of systematic and random errors in 32 HNC patients treated with IMRT using CBCT. It optimised the CTV to PTV margin using the NAL protocol and found that the PTV margin was 0.5-0.6 cm.…”
Section: Discussionmentioning
confidence: 99%